Applying QoS in FaaS applications: a software product line approach - Serrano Gutiérrez, Pablo; Ayala-Viñas, Inmaculada; Fuentes-Fernández, Lidia (My University, 2022)
A FaaS system offers numerous advantages for the developer of microservices-based systems since they do not have to worry about the infrastructure that supports them or scaling and maintenance tasks. However, it is not easy to apply quality of service (QoS) policies in these kind of applications. The high number of functions that an application can have and its various implementations introduce a high variability that requires a mechanism to decide which functions are more appropriate to achieve specific goals. We propose a Software Product Line based approach that uses feature models that model the application’s tasks and operations, considering the family of services derived from the multiple functions that can perform a specific procedure. Through an optimization process, the system obtains an optimal configuration that it will use to direct service requests to the most appropriate functions to meet certain QoS requirements.
Keywords: Soporte lógico - Desarrollo; Comunicaciones; Sonido - Transmisión; FaaS; QoS; SPL; Microservices